MGIMO-UNIVERSITY MASTER’S DEGREE IN POLITICAL SCIENCE ”POLITICS AND ECONOMICS IN EURASIA” (Сравнительная политика)
MGIMO-University Master’s Degree in Political Science ”Politics and Economics in Eurasia”.